Eksplorasi Binahong (Anredera Cordifolia (Ten.) Steenis) Batang Hijau dan Merah: Studi Organoleptik, Mikroskopis dan Skrining Fitokimia - Hesti Purwaningsih; Ruth C Nababan; Firmansyah, Yura Witsqa (Jurnal Serambi Engineering, 2025)
There are two types of binahong, namely red stem binahong and green stem binahong, but the scientific name of these two types is the same, namely Anredera cordifolia (Ten.) Steenis. This research aims to carry out organoleptic, microscopic identification and phytochemical screening on the leaves, stems and tubers of red stem binahong and green stem binahong. The data obtained were analyzed qualitatively descriptive. The results of organoleptic research on green stem and red stem Binahong leaves have a heart shape, pointed tip, thin limp leaf blades, smooth surface and slimy. Soft stems, cylindrical shape, twisted together. The shape of the tuber resembles a rhizome, has soft flesh. However, the surface of the leaves and stems of red stem binahong is thicker than green stem binahong. The results of microscopic examination showed that the leaves contain epidermal tissue, oxalate crystals and vascular bundles. The stem contains epidermis, parenchyma and vascular bundles. The tuber contains parenchyma, vascular bundles and ergastic matter in the form of starch. The results of phytochemical screening of the green leaves of Binahong plant were positive for containing flavonoids, saponins, tannins and steroids. The positive stem part contains saponins and tannins. And the positive tuber part contains alkaloids, flavonoids, saponins and tannins. Furthermore, in red stem binahong, the leaf part was positive for containing flavonoids, tannins and terpenoids and the stem part was positive for containing flavonoids and tannins.